The growth-promoting and disease-suppressing mechanisms of Trichoderma inoculation on peanut seedlings - Wang, Xingqiang; Zhao, Zhongjuan; Li, Hongmei; Wei, Yanli; Hu, Jindong; Yang, Han; Zhou, Yi; Li, Jishun (Frontiers in Plant Science, 2024)
Trichoderma spp. is known for its ability to enhance plant growth and suppress disease, but the mechanisms behind its interaction with host plants and pathogens remain unclear. This study investigated the transcriptomics and metabolomics of peanut plants (Arachis hypogaea L.) inoculated with Trichoderma harzianum QT20045, both in the absent and present of the stem rot pathogen Sclerotium rolfsii JN3011. Under normal conditions without pathogen stress, the peanut seedlings inoculated with QT20045 showed improved root length and plant weight, increased indole acetic acid (IAA) production, and reduced ethylene level with more active 1-aminocyclopropane-1-carboxylate acid (ACC) synthase (ACS) and ACC oxidase (ACO), compared with the non-inoculated control. Under the pathogen stress, the biocontrol efficacy of QT20045 against S. rolfsii was 78.51%, with similar effect on plant growth, and IAA and ethylene metabolisms to the condition with no biotic stress. Transcriptomic analysis of peanut root revealed that Trichoderma inoculation up-regulated the expression of the certain genes in IAA family, but down-regulated the genes in ACO family (AhACO1 and AhACO) and ACS family (AhACS3 and AhACS1), consistently in the absent and present of pathogens. During pathogen stress, QT20045 inoculation lead to the down-regulation of the genes in the Pectinesterase family to keep the host plant's cell wall stable, along with upregulation of the AhSUMM2 gene to activate plant defense responses. In vitro antagonistic test confirmed that QT20045 suppressed S. rolfsii growth through mechanisms of mycelial entanglement, papillary protrusions, and decomposition. Our findings highlight that Trichoderma inoculation is a promising tool for sustainable agriculture, offering multiple benefits from pathogen control to enhanced plant growth and soil health.